Optimization of Communication of Weather Forecast Information for the Province of the Special Region of Yogyakarta Via the Instagram Account @Infobmkgyia - Try kurnia Erlianto (Syntax Idea)
This research aims to optimize the communication of the Meteorology, Climatology, and Geophysics Agency (BMKG) in the Special Region of Yogyakarta Province through social media, with a focus on the case study of the Instagram account @infobmkgYIA. Effective communication in delivering weather forecasts, early warnings, and climate conditions is crucial to enhance public preparedness for natural disasters. The research methodology involves content analysis and user interaction on the Instagram account @infobmkgYIA. Data is collected to evaluate the most effective types of content, user participation levels, and their impact on increasing public awareness. This study adopts a qualitative research approach with the goal of deepening the understanding of the most effective types of content in conveying meteorological information, comprehending user participation levels, and assessing their impact on increasing public awareness. Data for this research is collected through content analysis obtained from the Instagram account @infobmkgYIA, including weather data visualizations, early warnings, and related information. Qualitative analysis is conducted to understand how the delivery of information can be optimized for greater effectiveness in achieving BMKG's communication goals. Direct interviews with relevant personnel at BMKG are not conducted in this research. Instead, information is obtained from reliable sources on the internet, such as official reports, articles, and other relevant information related to the research focus. The research also applies statistical analysis to support the understanding of inhibiting and driving factors in social media communication. Through this qualitative approach, it is expected that strategic recommendations will be identified to enhance the effectiveness of BMKG communication on social media platforms, especially on the Instagram account @infobmkgYIA